Risk-taking, Trust, and Traumatization of Refugees in Germany – A Field Experiment - Nora El Bialy; Andreas Nicklisch; Stefan Voigt (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We ran a number of experiments among refugees and Germans.In a first step, we ask whether refugees and Germans behave differently and find that risk preferences do not significantly differ between them. However, refugees are less trusting than Germans. In a second step, we seek to identify the factors determining the behavior of refugees and find that attributing a high importance to religion as well as having lived in a tent or container in Germany are associated with lower trust levels.
Keywords: C93; D74; O15; Z12; 330